Choosing the safest acute therapy during chronic migraine prophylactic treatment: pharmacokinetic and pharmacodynamic considerations. (2nd April 2016) - Lionetto, Luana; Borro, Marina; Curto, Martina; Capi, Matilde; Negro, Andrea; Cipolla, Fabiola; Gentile, Giovanna; Martelletti, Paolo
ABSTRACT: Introduction : Drugs used in the treatment of migraine have been reported to be highly associated with the occurrence of clinically significant drug-drug interactions (DDIs). Multiple drug therapy regimens are used for migraine treatment, particularly for chronic migraine. In fact, additional pharmacological agents are usually administered during an acute migraine attack in patients chronically treated with the prophylactic therapy. The variety of drugs available for migraine prophylactic and acute treatment, and consequently their pharmacological interactions, might complicate the choice of a safe combination therapy. Areas covered : This study discusses the prophylactic-acute DDIs from a pharmacokinetic and pharmacodynamic perspective, particularly interactions between antiepileptic drugs, tricyclic antidepressants, β-blockers, calcium channel blockers, triptans, nonsteroidal anti-inflammatory drugs and ergot derivatives. The available online tools have been used to evaluate the clinically significant DDIs. Expert opinion : The interactions between different drugs might be accurately predicted by the huge and detailed knowledge about the molecular pathways involved in pharmacodynamics and pharmacokinetics. Pharmacogenomic research has shed further light onto the mechanisms involved in the inter-individual variation in drug response and DDIs. Based on this knowledge, this paper will provide suggestions to improve the appropriateness of the drug choice in the prescription of preventative and acute migraine medications.